IMPLEMENTASI METODE WATERFALL DALAM SISTEM INFORMASI PELAYANAN PASIEN PADA KLINIK RAHMAH SKIN CARE - Zaeny Miftah; Eri Novitasari; Mesra Betty Yel (STIKOM CKI, 2022)
The process of data administration and medical history is a important thing in the world of medical health is important in the medical world. Patient data and medical records can be used as a reference for patient health checks and services obtained by patients. At the Rahmah Skin Care clinic, data processing such as patient data, medical records, and payment transactions that are stored still uses a manual process and often encounters several problems, such as lost data, patient cards left behind, damaged books, and if you have to search for data you have to open so much file and if it has happened like that the front office makes a new patient card. Researchers used the waterfall method to design a web-based patient service application. the researcher can conclude that with a new service administration information system, it can improve existing problems and make it easier for officers to enter patient data. With the research the author hopes to overcome the problems contained in the Rahmah Skin Care clinic.